Formulation of an integrated social commerce framework to promote social capital for energy sectors - Mohana Shanmugam; Vinitha Karunakaran; Asra Amidi (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Social capital refers to the resources available in personal and business networks. In developing a culture that values and practices social capital, social factors are considered one of the main precursors.  With the proliferation of social commerce and the maturing of social media, social capital can be acquired and further developed for productive benefits, particularly for energy sectors in Malaysia. In this study, an integrated social commerce framework to promote social capital is presented and evaluated. The framework attempted to define the relationship between the Theories of Planned Behavior (TPB) and Social Support Theory (SST) alongside satisfaction and perceived value factors towards promoting social capital development in energy sectors. This research uses SPSS to analyse the data collected from employee in the energy sectors in Malaysia. Research reveals that social capital is present when there is trust and loyalty among the users and the significance of social capital is monumental for energy sectors’ productivity, efficiency and profitability. A survey is adapted and distributed to 20 respondents from the energy sector in Malaysia as a mean to study on the validity and reliability of the research factors. Results indicate that all proposed factors are significant in promoting social capital except one, which is the Perceived Behavioral Control (PBC) of the TPB.